Independência funcional de pacientes com AIDS acometidos por neuroinfecções atendidos na rede Sarah do Brasil - Ferreira, Maryfranci Silva (2017)
Background: HIV / AIDS remains one of the greatest challenges facing health systems around the world. Among the major organic systems that can be affected by this virus, with repercussions on the quality of life of these individuals, the respiratory system, the gastrointestinal tract and the nervous system are highlighted, and the latter, leading to serious functional complications. In Brazil, sequelae related to opportunistic diseases of the CNS, such as neurotoxoplasmosis, tuberculous meningitis and neurocryptococcosis are important causes of cognitive and psychiatric damages. Evidence presents neurological complications as frequent conditions in the context of HIV / AIDS, where cerebral toxoplasmosis is the most prevalent etiology. However, there are few studies about the functional capacity of the patients affected by these pathologies. Objectives: To characterize the evolution of the functional independence of adult patients with HIV / AIDS affected by neuroinfections seen in a reference program in rehabilitation in Brazil. Method. Electronic records and the Functional Independence Measure (MIF) scale of neuroinfection patients with HIV / AIDS who completed hospitalization for rehabilitation from January 2006 to January 2016 at the SARAH Network of Brazilian Hospitals were reviewed. The variables with p <0.05 were considered significant. Results: Of 573 cases of neuroinfections, 81 had HIV / AIDS; Of these, 41 were included in the study. Males accounted for 51.22% of cases, mean age of neuroinfection was 35 years, and 29.27% had age equal to or less than 29 years. The diagnosis of HIV was made at the time of neuroinfection in 58.54% of the patients, and neurotoxoplasmosis was the most prevalent etiology in 75% of cases; 53.7% reported the occurrence of other associated opportunistic infections, of which 13.6% were pulmonary tuberculosis. The mean time from HIV diagnosis to admission was 48 months and the mean time between NI diagnosis and admission to rehabilitation was 37 months. At admission, 48.78% of the patients had dependency with up to 25% on the task, 31.15% had assisted dependence up to 50% in the task and 17.07% had complete independence on the MIF scale. Patients with multiple alterations in the neuroimaging tests (65.85%; n = 27) had a lower total MIF admission score (p <0.005). After discharge, cognitive, motor and total MIF scores were increased in both dependent and independent groups (p <0.005), despite the functional impairment presented at admission. Patients who spent more days in the rehabilitation program achieved greater gains in motor FIM (p = 0.04) and total FIM (p = 0.07), and those in a higher amount of medication had a higher gain in FIM scores Cognitive function (p = 0.02). Conclusions: The data presented evidences that NI in patients with HIV / AIDS can be responsible for significant functional impairment, reduces activity and restricts social participation. However, it was observed through the Functional Independence Measure (FIM) that the rehabilitation was able to produce motor and cognitive gains independent of the total score at admission and from the late period to the beginning of this intervention. The inclusion of disability surveillance and rehabilitation programs in public policies aimed at people living with HIV / AIDS is considered fundamental.